Significant variations in the cervical cancer screening rate in China by individual‐level and geographical measures of socioeconomic status: a multilevel model analysis of a nationally representative survey dataset. (24th March 2018) - Bao, Heling; Zhang, Lei; Wang, Limin; Zhang, Mei; Zhao, Zhenping; Fang, Liwen; Cong, Shu; Zhou, Maigeng; Wang, Linhong
Abstract: Variations in cervical cancer screening rates in China have rarely been studied in depth. This study aimed to investigate cervical cancer screening rates in relation to both individual‐level and geographical measures of socioeconomic status (SES). Data were obtained from women aged 21 years or older by face‐to‐face interviews between August 2013 and July 2014 as part of the Chinese Chronic Diseases and Risk Factors Surveillance. The geographical variables were obtained from the 2010 Chinese population census. The cervical cancer screening rates and 95% confidence interval (CI) were estimated and mapped. Multilevel logistic regression models were fitted. Overall, only 21.4% (95% CI: 19.6–23.1%) of 91, 816 women aged ≥21 years reported having ever been screened for cervical cancer and significant geographical variations at both province and county levels were identified ( P < 0.01). The cervical cancer screening rates were the lowest among the poor [13.9% (95% CI: 12.1–15.7%)], uninsured [14.4% (95% CI: 10.3–18.4%)], less‐educated [16.0% (95% CI: 14.3–17.6%)], and agricultural employment [18.1% (95% CI: 15.8–20.4%)] women along with those residing in areas of low economic status [15.0% (95% CI: 11.8–18.2%)], of low urbanization [15.6% (95% CI: 13.4–17.7%)], and of low education status [16.0% (95% CI: 14.0–18.1%)]. The multilevel analysis also indicated that women with lower individual‐level measures of SES residing in areas with low geographical measures of SES were significantly less likely to receive cervical cancer screening ( P < 0.0001). Despite the launch of an organized cancer screening program in China, cervical cancer screening rates remain alarmingly low and significant variations based on geographical regions and measures of SES still exist. It is therefore essential to adopt strategies to better direct limited available public resources to priority groups. Abstract : Despite the launch of an organized cancer screening program in China, population‐based cervical cancer screening rates remain alarmingly low and significant variations based on geographical regions and measures of SES still exist. It is therefore essential to adopt strategies to better direct limited available public resources to priority groups.